Integrating Cybersecurity into Veterinary Medicine: Protecting Animal Health Data and Systems (Research, Society and Development, 2025)
Cyberbiosecurity is an emerging field at the convergence of life sciences and the digital world. The aim of this study is to analyze the importance of cyber security for veterinary clinics, practices, laboratories and hospitals by presenting the dangers, consequences and methodologies for defending against cyber attacks. During the practice of veterinary medicine, the storage of a significant amount of high-value data makes veterinary practices, clinics, laboratories and hospitals significant targets for cybercriminals. Currently, veterinary institutions have been victims of cyber attacks mainly through suspicious emails (phishing), text messages (smishing) and voice calls (vishing). Therefore, it is of fundamental importance to implement security measures that can protect veterinary institutions from attacks by cybercriminals.